Platform development for primary blast injury studies - Nguyen,TN; Sory,DR; Rankin,SM; Proud,WG; Amin,HD (Trauma (United Kingdom), 2018)
© 2018, The Author(s) 2018. Explosion-related injuries are currently the most commonly occurring wounds in modern conflicts. They are observed in both military and civilian theatres, with complex injury pathophysiologies. Primary blast injuries are the most frequently encountered critical injuries experienced by victims close to the explosion. They are caused by large and rapid pressure changes of the blast waves which produce a wide range of loading patterns resulting in varied injuries. Well-characterised experimental loading devices which can reproduce the real mechanical characteristics of blast loadings on biological specimens in in vivo, ex vivo, and in vitro models are essential in determining the injury mechanisms. This paper discusses the performance and application of platforms, including shock tubes, mechanical testing machines, drop-weight rigs, and split-Hopkinson pressure bar, with regards to the replication of primary blast.